USER EXPERIENCE ANALYSIS OF SMART PHONE USERS IN EXPLORING AND READING NONFICTION BOOKS - Fuad Wahdan Muhibuddin; Popong Nurhayati; Mohamad Sahid Rahman (Business Review and Case Studies, 2021)
Indonesia has a high penetration users of smart phone occupied 4th position behind China, India, and US. The utilization of smart phone should be contributed positive matter to its users, once increasing reading habbit. We argued that so important to user to find some nonfiction books information related to their needs and desires, and high potential platform business model development. This paper aims to map a relation between users experience in exploring and reading of nonfiction books to platform business development opportunities. The study was human centre and qualitative approach, conducted by user experience analysis with empathy mapping canvas and customer journey mapping approach, then conducted mind mapping for synthesis problems as user experiences. The result shown the frequently user problems are lacked of nonfiction books information, lacked of reading motivation, constrained on purchasing or rent the book, lacked of book reading management. By solving those problems should drive to ideate developing platform based human centered design and shown highly potential market platform for special user book reader and generally smart phone users. Keywords: user experience, human centre, empathy map canvas, customer journey mapping